Dampak Struktural dari Pertumbuhan Sektor Industri dan Perdagangan terhadap Penyerapan Tenaga Kerja di Indonesia: Proyeksi Tahun 2003-2007 - Nikensari, Sri Indah (Jurnal Ekonomi dan Pembangunan Indonesia, 2004)
Economic growth give some hope on labor absorbtion in economic sectors. It can be seen from trends after crisis that unemployement is rising overtime. This study tends to look on structural impact of growth in industrial and trade sector to labor absorption in Indonesia. The result is labor absorption projection in economic sectors within 2003-2007.